Practical Visualization of Local Vibration Data Collected over Large Concrete Elements. (7th March 2014) - Oh, Taekeun; Popovics, John S.
Abstract In this article, an original multidimensional presentation format for nondestructive evaluation point test spectral data is proposed. Time domain signals from air‐coupled impact‐echo (IE) tests are transformed into the frequency domain and arranged along x and y coordinates of the tested surface to give a 3‐D data set volume. Spectral amplitude is indicated by gray scale, giving rise to a "fourth" dimension of information within the data volume. This presentation, which stacks data in both spatial and spectral domains, includes all spectral data up to a natural frequency threshold (5–6 kHz) to isolate the response generated by near‐surface delamination defects. Visual interpretation of the dense data set of spectral information within the volume is enabled by incorporating transparency/opacity control on the data set, where higher spectral amplitudes are associated with more opacity. Consistent rule‐based criteria for optimal image parameter determination for a given test structure are established to optimize application for defect detection. Application of this data manipulation and visualization technique to IE data collected from two different reinforced concrete samples demonstrates improved near‐surface delamination detection as compared with conventional data presentation formats.